'New trade union strategies for new forms of employment': Focus on Italy. Issue 3 (September 2019) - Gramano, Elena; Gaudio, Giovanni
The article aims at providing an exhaustive description of the current scope of application of labour law, with the goal to assess who is entitled to exercise fundamental labour and social rights within the Italian legal system. More specifically, this assessment is used to test the main hypothesis of the Authors of the ETUC report 'New trade union strategies for new forms of employment', according to which the idea of the 'personal work relation' may be used to redefine the personal scope of application of labour law as applicable to any person that is ' engaged by another to provide labour, unless that person is genuinely operating a business on her or his own account' . The article concludes that, although the Italian legal system cannot be currently reframed around the idea of the 'personal work relation', there are few signs under Italian law of a trend of enlarging the scope of application of labour laws in order to apply certain traditional labour rights not only to employees but also to certain types of independent contractors.